Acute proptosis in a diabetic patient: diagnostic and therapeutic dilemmas - Khairul-Anwar, Ibrahim; Tai, Evelyn; Hussein, Adil; Zunaina, Embong (Cureus Inc, 2021)
An elderly diabetic lady presented with a painful swollen right eye and blurred vision for one week, preceded by right eye redness for six months. Her right eye best-corrected visual acuity was finger counting at 1 m. There was right eye proptosis, limited extraocular muscle movements, corkscrew vessels, chemosis and elevated intraocular pressure, but no bruit. Fever was absent. Computed tomography of the brain and orbit showed thickened extraocular muscles and intraconal fat streakiness, with normal superior ophthalmic vein and concavity of the cavernous sinus. Intravenous antibiotics resulted in limited clinical improvement. The subsequent response to oral prednisolone was dramatic, with the improvement of visual acuity to 20/60 after three doses. In cases of atypical orbital cellulitis where antibiotics fail, one should consider differential diagnoses such as orbital inflammatory disease, vascular anomalies and masqueraders. We discuss the approach to the diagnosis of acute proptosis in a diabetic patient and highlight the role of corticosteroids in idiopathic orbital inflammatory disease.